Barrier permeability at cut axonal ends progressively decreases until an ionic seal is formed. - Eddleman, C S (2000)
After axonal severance, a barrier forms at the cut ends to rapidly restrict bulk inflow and outflow. In severed crayfish axons we used the exclusion of hydrophilic, fluorescent dye molecules of different sizes (0.6-70 kDa) and the temporal decline of ionic injury current to levels in intact axons to determine the time course (0-120 min posttransection) of barrier formation and the posttransection time at which an axolemmal ionic seal had formed, as confirmed by the recovery of resting and action potentials. Confocal images showed that the posttransection time of dye exclusion was inversely related to dye molecular size. A barrier to the smallest dye molecule formed more rapidly (<60 min) than did the barrier to ionic entry (>60 min). These data show that axolemmal sealing lacks abrupt, large changes in barrier permeability that would be expected if a seal were to form suddenly, as previously assumed. Rather, these data suggest that a barrier forms gradually and slowly by restricting the movement of molecules of progressively smaller size amid injury-induced vesicles that accumulate, interact, and form junctional complexes with each other and the axolemma at the cut end. This process eventually culminates in an axolemmal ionic seal, and is not complete until ionic injury current returns to baseline levels measured in an undamaged axon.